2021
DOI: 10.3389/fmicb.2021.666940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gut Microbiota of Yaks From Different Geographical Regions

Abstract: Gut microbiota are closely linked to host health and adaptability to different geographical environments. However, information on the influence of different geographical conditions on the intestinal microbiota of yaks is limited. In this study, 18 yak fecal samples were collected from three regions of China, namely Shangri-la, Lhasa, and Yushu, and were analyzed via high-throughput sequencing. The alpha diversity, as measured by the Shannon, ACE, and Chao indices, was the highest in the Shangri-la samples. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…As observed previously ( Zhang et al, 2016 ; Guo et al, 2021 ; Liu et al, 2021 ), Bacteroidetes and Firmicutes were the dominant taxa identified in this study. Guo et al (2020) reported that Bacteroidetes were the most important bacteria in yak rumen from birth to adulthood.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As observed previously ( Zhang et al, 2016 ; Guo et al, 2021 ; Liu et al, 2021 ), Bacteroidetes and Firmicutes were the dominant taxa identified in this study. Guo et al (2020) reported that Bacteroidetes were the most important bacteria in yak rumen from birth to adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…Taking into account those and the present results, it appears that yaks in the MAL group are more efficient at utilizing their pasture and emit less methane. As observed previously (Zhang et al, 2016;Guo et al, 2021;Liu et al, 2021), Bacteroidetes and Firmicutes were the dominant taxa identified in this study. Guo et al (2020) reported that Bacteroidetes were the most important bacteria in yak rumen from birth to adulthood.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Bacteroidetes members are the most important bacteria in the rumen from birth to adulthood, and Firmicutes members are crucial for energy conversion. They are important for the digestion of proteins and carbohydrates, respectively ( Liu W. et al, 2021 ). From the above results, the beta diversity between the LA and HA groups was also significantly different.…”
Section: Discussionmentioning
confidence: 99%